The Apostles’ and the Athanasian Creeds in the Religious Writings of the Metropolitanate of Kiev (16-17 th. centuries) - Korzo Margarita (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The study considers what status in the religious writings of the Metropolitanate of Kiev and Russia of the 16–17th centuries had two old Christian creeds — the Apostles’ and the Athanasian. As main sources are examined printed editions of the Orthodox Brotherhood of Vilnius, catechisms by Lavrentĳ Zyzanĳ (1627) and by the Orthodox metropolitan of Kiev Peter Mohyla (1645), manuscript catechetical manual «Veniets Very» (1670) and two printed catechisms by Simeon Polotskiy. All authors that belonged to the so-called Kievan theological school accepted the Apostles’ Creed as an authentic one and used it as a basis for their presentation of Christian doctrine. A similar role the given creed played in the Catholic Church and in all Protestant denominations. The Moscow tradition, which presented by the manuscript heritage of Euthymeos of Chudov (Moscow State Historical Museum, the Synodal Collection) attributed the Apostles’ Creed as a heretic confession by Marcellus and denied its use in catechetical and liturgical practices. A completely diﬀerent status got the confession attributed to Athanasius of Alexandria. The given creed was borrowed in the Moscow tradition through Kievan editions, was printed in Psalters (since 1647) and school primers (since Both in the religious writings of the Metropolitanate of Kiev and Russia the creed was used mainly for polemical purposes (initially in a controversy with Antitrinitarians later — with the Old Believers).